Spectacula contemplationis (1244-46): A Treatise by Thomas Gallus - Lawell, Declan (Recherches de théologie et philosophie médiévales, 2009)
This article presents for the first time a critical edition of a minor treatise named Spectacula contemplationis or The Spectacles of Contemplation by Thomas Gallus. The treatise’s aim is to describe the various levels of knowledge that are traversed by the soul in its ascent to God. By the author’s own admission, the treatise is inspired by the six types of contemplation listed by Richard of St Victor in his work on contemplation, Beniamin maior. Gallus’s treatment however is not just a repetition of the material covered by his fellow Victorine. Though short in length, the treatise reveals some original developments and major points of divergence from Richard’s intellectual approach, which reflect the affective Dionysianism of the Abbot of Vercelli. It also calls to mind features of Hugh of St Victor’s De tribus diebus and Bonaventure’s Itinerarium mentis in Deum, as well as revealing the previously neglected fact that Gallus may have been the author of, or at least wrote a commentary on, a sequence entitled Super mentem exultemus.\n4207 \n4207